A Linguagem da Inclusão/Exclusão Social-Escolar na História, nas Leis e na Prática Educacional - Fidalgo, Sueli Salles (2006)
This thesis dissertation was carried out in the intersection of the Critical Applied Linguistics (Rajagopalan, 2003), Critical Theory (Habermas, 1985, Heller, 1970) and Critical Pedagogy (Freire, 1970) areas of knowledge production. It aims at investigating the language employed either to include or exclude the members of educational contexts in Brazil. This is seen in the school organization, historically speaking, through the analysis of laws and public policies that have, traditionally been prescribing the work developed within the public school environment. In other words, this dissertation aims at discussing school inclusion as it has been practiced throughout history, and, more precisely, in the last few years, when the term has been defined and implemented, so as to verify if, by what means and in which instances the project of school inclusion has led to social inclusion especially of educators and students. Theoretically speaking the text is base don the dialogical understanding of language (Bakhtin/Volochinov, 1929), the theory of communicative action (Habermas, 1985), the historical constructs of social and school organization (Schwarcz, 1993; Patto, 1999; Hobsbawn, 1995), developmental constructs (Vygotsky, 1930, 1934; Leontiev, 1959), a collaborative perspective of teacher education (Magalhães, 2005) so as to strengthen the understanding of what might be an inclusive practice. In order to discuss a possible inclusive practice, one would evidently have to discuss issues that historically have been the chore of exclusion, since inclusion would never have become an issue for laws and discourses if not for the predominance of exclusion in our society. In methodological terms, this dissertation is based on a critical perspective as well, i.e., it is a piece of work that aims at contributing to the transformation of the status quo. Its methodology is then partially defined by the Critical Hermeneutic concepts (Ricouer, 1986) and, partially, by a Critical-Collaborative perspective (Magalhães, 2002a, 2002b, 2005) the former as a means to understanding data generation and treatment and the latter relating to the means by which the project was re-designed several times by the joint action of participants. The data reveals that school inclusion, in Sao Paulo, is not leading to the social inclusion of children. Besides it has been leading to the exclusion of teachers who are not being educated to work within the current school diversity